The predominant role of 18F-FDG PET/CT over MDCT in assessment of ovarian cancer patient - Hemat A. Mahmoud (The Egyptian Journal of Radiology and Nuclear Medicine, 2015)
Objectives: This article discusses that FDG PET/CT is superior to MDCT in evaluation of ovarian cancer oncological evaluation. Patients and methods: 87 PET/CT scans of 64 women with clinically suspected or pathologically proven ovarian cancer were retrospectively analyzed. The findings of contrast enhanced MDCT (CE-CT) were interpreted by two experienced radiologists unaware of PET/CT findings. At least two experienced nuclear medicine physicians who were unaware of CE-MDCT findings examined PET images, evaluating localization and characterization and comparing them to co-registered PET/CT images. Diagnostic accuracy was determined on a patient level and a region level. Results: PET has significantly higher Sensitivity, specificity, PPV, NPV, and overall accuracy of 94.7%, 86.7%, 93.1%, 89.7%, and 91.9% respectively compared to 89.5%, 30%, 70.8%, 60% and 68.9% for MDCT on patient level. The diagnostic performance of PET was also better at most anatomical sites when results were analyzed on region level. Conclusions and recommendations: FDG PET in addition to conventional imaging modalities should represent an important step in the diagnostic flowchart of ovarian cancer patients for evaluating abdominal and extra-abdominal probable metastatic deposits.